Stabilization of active ultrathin amorphous ruthenium oxide via constructing electronically interacted heterostructure for acidic water oxidation - Xiangxiang Pan; Huidong Qian; Jiansheng Xu; Haifeng Wang; Han-Don Um; Chao Lin; Xiaopeng Li; Wei Luo (Green Energy & Environment)
Amorphous RuOx (a-RuOx) with disordered atomic arrangement and abundant coordinatively unsaturated Ru sites possesses high intrinsic electrocatalytic activity for oxygen evolution reaction (OER). However, the a-RuOx is prone to fast corrosion during OER in strong acid. Here, we realized the stabilization of an ultrathin a-RuOx layer via constructing heterointerface with crystalline α-MnO2 nanorods array (MnO2@a-RuOx). Benefiting from the strong electronic interfacial interaction, the as-formed MnO2@a-RuOx electrocatalyst display an ultralow overpotential of 128 mV to reach 10 mA cm−2 and stable operation for over 100 h in 0.1 mol L−1 HClO4. The assembled proton exchange membrane (PEM) water electrolyzer reach 1 A cm−2 at applied cell voltage of 1.71 V. Extensive characterizations indicate the MnO2 substrate work as an electron donor pool to prevent the overoxidation of Ru sites and the OER proceeds in adsorbent evolution mechanism process without involving lattice oxygen. Our work provides a promising route to construct robust amorphous phase electrocatalysts.